PENINGKATAN KETERAMPILAN SISWA SMA/MA BIDANG SAINS DAN TEKNOLOGI MELALUI PELATIHAN ROBOTIKA BERBASIS MIKROKONTROLLER - Hozairi Hozairi; Akhmad Arif Kurdianto (Community Development Journal, 2019)
Senior High School, hereinafter abbreviated as SMA, is a formal education unit that organizes general education. The problem experienced by high school in Pamekasan Regency is that there are still 25% of graduates from high school who do not continue their studies, so they become less productive because they do not have skills.To help solve problems for high school students who do not continue to need special skills, it is necessary to design and compile an effective and efficient training model that is able to help high school graduates enter the business world and industry. Based on the analysis of the potential of the Pamekasan region and the potential development of the business and industry, the most suitable training to be developed is robotics training. The stages of the training start from (1) the participant registration process, (2) the process of selecting participants, (3) pre-test, (4) conducting training (assembly and programming) robots, (5) post test and (6) results analysis. The results of the analysis of the implementation of the training for 14 (fourteen) hours resulted in the following progress reports: (enough = 13%), (good = 49%) and (very good = 38%). This means that the results of the community service program have provided excellent outcomes for the improvement of skills and skills for all high school students in Pamekasan Regency.